2022
DOI: 10.3389/fimmu.2022.961933
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of cancer immunotherapy through pyroptosis: A pyroptosis-related signature predicts survival benefit and potential synergy for immunotherapy in glioma

Abstract: BackgroundPyroptosis is a critical type of programmed cell death that is strongly associated with the regulation of tumor and immune cell functions. However, the role of pyroptosis in tumor progression and remodeling of the tumor microenvironment in gliomas has not been extensively studied. Thus, in this study, we aimed to establish a comprehensive pyroptosis-related signature and uncover its potential clinical application in gliomas.MethodsThe TCGA glioma cohort was obtained and divided into training and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…We compared our model with several other prognostic models to assess the importance of the PANoptotic score for predicting the prognosis of glioma. The results showed that the prediction accuracy of our model was better than other models that have been reported (Chen et al, 2021;Liu P. et al 2022;Zeng et al, 2022) (Figures 5D-F and Supplementary Figures S5A-F).…”
Section: Development and Validation Of A Panoptotic Score Model Based...mentioning
confidence: 55%
See 1 more Smart Citation
“…We compared our model with several other prognostic models to assess the importance of the PANoptotic score for predicting the prognosis of glioma. The results showed that the prediction accuracy of our model was better than other models that have been reported (Chen et al, 2021;Liu P. et al 2022;Zeng et al, 2022) (Figures 5D-F and Supplementary Figures S5A-F).…”
Section: Development and Validation Of A Panoptotic Score Model Based...mentioning
confidence: 55%
“…In previous studies, transcriptomics-based prognostic models for glioma have also been proposed. For example, Chen et al constructed a prognostic model of glioblastoma based on the function of STEAP (Six-transmembrane epithelial antigen of the prostate) family, STEAP2-and STEAP3-based prognostic risk score ( Chen et al, 2021 ); Zeng et al researched a prognostic model of glioma based on pyroptosis named pyroptosis-related risk signature (PRRS) ( Zeng et al, 2022 ); Liu P. et al (2022) proposed a prognostic model of glioma based on m6A regulators model called risk score, etc. The predictive performance of our constructed model was better than each of the above models by comparison of area under the ROC curve (AUC).…”
Section: Discussionmentioning
confidence: 99%
“…Targeting Bcl-2 and/or activating BAX to restore caspase-3 activity may be a potential therapeutic strategy for glioma [ 26 , 27 ]. Several strategies, such as small molecule inhibitors, gene therapy, and immunotherapy, have been explored to modulate BAX and Bcl-2 expression and restore caspase-3 activity in glioma cells, with promising results in preclinical studies [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%